Local immune response to gastric Campylobacter in non-ulcer dyspepsia. - Wyatt, J I (1986)
Colonising Campylobacter pyloridis were identified histologically in gastric biopsy specimens from 89% of 83 patients with non-ulcer dyspepsia and chronic gastritis, but not in 58 dyspeptic patients with normal mucosa. The presence and population density of organisms was associated with the presence of intraepithelial neutrophils. In vivo coating of the organisms by host immunoglobulin was investigated by immunoperoxidase staining of IgA, IgG, and IgM in 54 biopsy specimens. IgA coated bacteria were seen in all cases of active gastritis, and in 60% of biopsy specimens without intraepithelial neutrophils. Coating with IgG or IgM, or both, was correlated with activity of gastritis and was rarely seen in the absence of a neutrophil infiltrate.